Burabay national park. Experiments in tourism, nationbuilding, and informal economy - Nurmukhanov, Nursultan (Nazarbayev University School of Sciences and Humanities, 2016)
This work analyzes how environment and society interact with each other focusing on the case of Burabay National Park. Based on the field research and numerous interviews, this work demonstrates how seemingly disparate notions of top-down nation-building and tourism development have shaped into a site with unique attributes. One part of the picture is the puzzle of how nation-building process fostered by other variables such as tourism development and environmental awe could give a birth to completely new objects of sacral landscape that operate in terms similar to other famous pilgrimage destinations in the Central Asia. The other part is development of the informal economy and a set of principals according to which the local society has to operate in order to be competitive in the National Park. I believe that the findings of this work could significantly contribute to the as yet very limited literature on tourism development in Kazakhstan as well as provide analysis of an interesting case of a nation-building process.
Бұрабай ұлттық паркі. Туризм, ұлт құрылысы, және бейресми экономикадағы эксперименттер
Национальный парк Бурабай. Эксперименты в туризме, конструкции нации, и неформальной экономике
Keywords: Burabay National Park; National Park; Национальный парк Бурабай; Бурабай; туризм; tourism